Southeast Asia : - Cady, John F. (McGraw-Hill, 1964)
This work cover the history of the peoples of Southeast Asia from early centuries A. D. to the end of World War II. The discussion encompasses the region east of India and south of China, extending from Burma on the west to the Philippines on the east and southward through the Indonesian archipelago.